2012
DOI: 10.1016/s2255-4971(15)30101-4
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis of the Scaphoid in Immature Skeletons

Abstract: This paper presents a review of the literature on pseudarthrosis of the scaphoid in skeletally immature individuals, taking into consideration its epidemiology, diagnosis and treatment, as well as its controversies. Knowledge of this subject makes it possible for patients to be given appropriate treatment immediately. Pseudarthrosis of the scaphoid in skeletally immature patients is a rare condition that results from error or lack of diagnosis of a fracture. Thus, careful clinical and radiographic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 36 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Pediatric scaphoid fractures are rare injuries, 41 representing between 2 and 3% of pediatric hand and wrist injuries (►Table 2). 1,5,[7][8][9]23 It remains the most common carpal bone to be fractured in all pediatric age groups. 36 Studies revealed an incidence of 0.4 per 100,000 females and 2 per 100,000 males.…”
Section: Epidemiology Of Scaphoid Fracturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Pediatric scaphoid fractures are rare injuries, 41 representing between 2 and 3% of pediatric hand and wrist injuries (►Table 2). 1,5,[7][8][9]23 It remains the most common carpal bone to be fractured in all pediatric age groups. 36 Studies revealed an incidence of 0.4 per 100,000 females and 2 per 100,000 males.…”
Section: Epidemiology Of Scaphoid Fracturesmentioning
confidence: 99%
“…With this management, 30% of those clinically suspected fractures were proven to be true fractures. 2,5,14 Around 45% of the suspected scaphoid fractures have the diagnosis confirmed on the first follow-up, 2 weeks after the injury, and 84% are evident 5 weeks after injury. 2,7 It has also been highlighted that MRI had a negative predictive value of 100% and avoided unnecessary radiation and immobilization in 58% of patients.…”
Section: Epidemiology Of Scaphoid Fracturesmentioning
confidence: 99%
See 3 more Smart Citations